THE MIXED LEGACY OF MAGNA CARTA FOR AMERICAN RELIGIOUS FREEDOM - Green, Steven K. (Journal of law and religion, 2017)
In 2015 Magna Carta celebrated its 800th anniversary. The Great Charter has been widely heralded as a fount of many rights that are highly valued in British and American law. One right that people have identified in the Carta is that of religious freedom. Magna Carta contains two provisions guaranteeing freedom of the church from government authority. In 2013, the United States Supreme Court relied on that authority in a ruling that affirmed the principle of religious autonomy. This article argues that relying on the legacy of Magna Carta for the principle of religious freedom is tenuous: the document had little influence on the development of the First Amendment. Even Magna Carta's authority for the principle of church autonomy is overstated, as the Carta had nothing to do with the development of that principle in American law. Finally, judicial reliance on Magna Carta for the principle of religious freedom risks elevating protections for religious institutions over the interests of individuals. As a result, the legacy of Magna Carta for the principle of religious freedom is mixed, at best.